Validity and reliability of a Thai version of the Body Image Scale among patients with post-coronary artery bypass graft - Pannawit Moonkaew; Rapin Polsook (Belitung Nursing Journal, 2023)
Background: Body image is a significant concern for patients who have undergone a coronary artery bypass graft (CABG) surgery, as the presence of scars on the chest, arms, and legs can impact their self-perception. Difficulty accepting these scars may lead to negative body image, non-compliance with prescribed treatments, and potentially poorer health outcomes. However, the Body Image Scale, commonly used to assess body image, has not been validated for Thai patients. Objective: This study aimed to evaluate the validity and reliability of the Body Image Scale in Thai post-CABG patients. Methods: This instrument validation study was conducted between April and July 2022. A total of 320 post-CABG patients were randomly selected to participate in the study. The scale was translated from English to Thai and adapted to address the concerns of CABG patients specifically. Validity and reliability were assessed using Principal Component Analysis and Cronbach’s alpha. Results: The Thai version of the Body Image Scale demonstrated satisfactory internal consistency, as indicated by a Cronbach’s alpha coefficient of 0.88. The factor analysis revealed a single-factor structure, and each component had communalities ranging from 0.63 to 0.76, explaining 70.07% of the variance in body image. Conclusion: The Thai version of the Body Image Scale exhibited good validity and reliability for assessing body image in Thai patients undergoing CABG surgery. Nurses and other healthcare professionals can effectively utilize this measurement tool to evaluate the body image concerns of Thai patients following a CABG procedure.